Re-envisioning Astraea: Myth and Vision in Jeremy Bentham’s “Blackstone Familiarized” - Claire Wrobel (XVII-XVIII)
Poetic and pictorial rewritings of the myth of Astraea have often sought to legitimize political regimes, with the return of the goddess of justice symbolizing the inauguration of a new golden age. Jeremy Bentham’s “Blackstone Familiarized” offers a fascinating counter-example. This unfinished essay presents a play transcribing a vision which had appeared to the reformer in a dream. The role of the goddess, who embodies “universal jurisprudence”, is here to reveal to the audience the real state of English institutions and to introduce the utilitarian principles which would make it possible to reform them. After analysing the processes used to transcribe the vision by drawing on the “visual turn” recently taken in the field of law and literature, the article shows how Bentham’s rewriting leads us to reconsider the ideological functions of myth and seeks to account for the unexpected appearance of another allegorical figure, namely the goddess of fiction.